(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
The Normal Pulmonary Artery (PA) systolic pressure of children and adults is < 30 mm Hg and the mean PA pressure is < 25 mm Hg at sea level. Pulmonary hypertension (PH) is defined as a mean pulmonary artery pressure > 25 mm Hg at rest or > 30 mm Hg during exercise. An increase in pulmonary flow, vascular resistance, or both can result in pulmonary hypertension. Pulmonary Arterial Hypertension (PAH) commonly arises in patients with Congenital Heart Diseases (CHD) are usually associated with increased pulmonary blood flow. Greater number of patients with Pulmonary Arterial Hypertension (PAH), associated with congenital heart disease, are now surviving into adulthood, many with increasingly complex cardiac defects. Patients with cardiac defects which result in left-to-right shunting tend to develop PAH, owing to the increased shear stress and circumferential stretch induced by pulmonary blood flow, which leads to endothelial dysfunction and progressive vascular remodeling followed by vascular resistance. Pulmonary hypertension in association with congenital heart diseases is seen in large systemicto- pulmonary communications such as Ventricular Septal Defect (VSD), Patent Ductus Arteriosus (PDA) atrioventricular septal defects, aorticopulmonary window defect etc. Pulmonary hypertension associated with large L-R shunt lesions (e.g. VSD, PDA) is called Hyperkinetic Pulmonary Hypertension (PH). It is the result of an increase in pulmonary blood flow, a direct transmission of the systemic pressure to the pulmonary artery, and compensatory pulmonary vasoconstriction. Hyperkinetic PH is usually reversible if the cause is eliminated before permanent changes occur in the pulmonary arterioles. If large L-R shunt lesions are left untreated, irreversible changes take place in the pulmonary vascular bed, with severe pulmonary hypertension and cyanosis due to a reversal of the L-R shunt. This stage is called Eisenmenger syndrome or Pulmonary Vascular Obstructive Disease (PVOD). Surgical correction is not possible at this stage. Due to lack of formal study which of the L-R congenital shunt is more commonly associated with the development of pulmonary hypertension is not known the cross-sectional study therefore intends to find the pattern of congenital L-R heart diseases commonly attributed to the development pulmonary hypertension. The diagnosis of the abovementioned congenital heart disease will be made by echocardiography. In this study, most of the participant [22 (44.0%)] were in the < 1 years age group, female were proportionately higher, most patients presented with cough and difficulty in breathing, dyspnoea and tachycardia were the most common clinical findings, murmur mostly systolic were found, Eisenmenger syndrome was not found in any child, ASD was the most common congenital anomaly. About four-fifth of the participants had single congenital anomaly. Two-fifth of the participant was found having severe PAH. Significant correlation were revealed between age group and Pulmonary arterial pressure (R= 0.775), Status of PAH was found significantly different (p< 0.05) in age groups and presence of number of anomalies. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 31-37